help_people
  • help_people
Two functions are shown in the table below. Function 1 2 3 4 5 6 f(x) = −x2 + 4x + 12 g(x) = x + 2 Complete the table on your own paper, then select the value that is a solution to f(x) = g(x). x = 2 x = 3 x = 5 x = 6
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
help_people
  • help_people
@triciaal @Elsa123
help_people
  • help_people
Hi :) no offense but are you almost done replying ?
LynFran
  • LynFran
ok u need to input the given values into the function eq. f(x)=-x^2+4x+12 so f(1)=-(1)^2+4(1)+12 ... g(x)=x+2 then g(1)=(1)+2 ...

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

help_people
  • help_people
f(2)=-2^2+4(2)+12 g(x)=2+2
help_people
  • help_people
f(3)=-2^3+4(3)+12 g(x)=3+2
help_people
  • help_people
f(4)=-2^4+4(4)+12 g(x)=4+2
LynFran
  • LynFran
u need to solve these...
help_people
  • help_people
could you at least help me :(?
LynFran
  • LynFran
ok f(1)=-(1)^2+4(1)+12 =-1+4+12 =15 g(1)=(1)+2 =3
help_people
  • help_people
f(2)=-4+8+12 f(2)=4+12 f(2)=12 g(2)=4
LynFran
  • LynFran
f(2)=-(2)^2+4(2)+12 =-(4)+8+12 =16 g(2)= (2)+2 =4
LynFran
  • LynFran
f(3)=-(3)^2+4(3)+12 =-9+12+12 =15 g(3)=3+2 =5
help_people
  • help_people
i did f(2) wrong so are we done knee what o i ahebv to do next?
LynFran
  • LynFran
f(4)=-(4)^2+4(4)+12 =-16+16+12 =12 g(4)= 4+2 =6 f(5)= -(5)^2+4(5)+12 = -25+20+12 =7 g(5)= 5+2 =7 f(6)= -(6)^2+4(6)+12 =-36+24+12 =0 g(6)=6+2 =8
LynFran
  • LynFran
f(x)=g(x) -x^2+4x+12=x+2 -x^2+4x-x+12-2=0 -x^2+3x+10=0 -(x+2)(x-5)=0 x+2=0 x=-2 and x-5=0 x=5 now which option is it?
LynFran
  • LynFran
did u realize that f(5) and g(5) are equal?
help_people
  • help_people
yes so x=5 is the option?
LynFran
  • LynFran
correct
help_people
  • help_people
ty! could you help with one more??
help_people
  • help_people
actually a couple tbh???

Looking for something else?

Not the answer you are looking for? Search for more explanations.